Pengaruh mekanisme corporate governance terhadap integritas laporan keuangan - Handayani, Tri; Budiantara, Martinus (LPMP Imperium, 2023)
The purpose of this research is to examine the influence of institutional ownership, managerial ownership, independent commissioners, and the audit committee on the integrity of financial reports. The research population consists of insurance sector companies listed on the Indonesia Stock Exchange from 2018 to 2021. The sampling method used is purposive sampling, with a total of 13 companies selected as samples. Data analysis techniques include classic assumption tests, such as normality tests, multicollinearity tests, autocorrelation tests, and heteroskedasticity tests. Hypothesis testing is conducted using multiple regression analysis. The results of this study indicate that institutional ownership, the audit committee, and independent commissioners have an impact on the integrity of financial reports, while managerial ownership does not have an impact on the integrity of financial reports Public interest statements This research is expected to serve as a valuable reference for enhancing understanding and knowledge in the field of accounting, as well as providing crucial information for investors and financial analysts in evaluating investment decisions related to companies.